Rabi oscillations in systems with small anharmonicity - Amin, M.H.S. (Физика низких температур, 2006)
When a two-level quantum system is irradiated with a microwave signal in resonance with the
energy difference between the levels, it starts Rabi oscillations between those states. If there are
other states close, in energy, to the first two, the microwave signal will also induce transitions to
those. Here we study the probability of transition to the third state, in a three-level system, while
Rabi oscillations between the first two states are performed. We investigate the effect of pulse
shaping on the probability and suggest methods for optimizing the pulse shapes to reduce the transition
probability.